2022
DOI: 10.3389/fmars.2022.895354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Posidonia oceanica traits along a temperature gradient in the Mediterranean Sea shows impacts of marine warming and heat waves

Abstract: Global warming and Marine Heat Waves (MHWs) are having large-scale impacts on the seagrasses and their effects on the Mediterranean endemic Posidonia oceanica need to be properly defined. This research aimed to sharpen the knowledge on P. oceanica response to the warming by correlating the shoot morphology and the productivity of the seagrass to temperature conditions and MHW occurrence. Two correlative studies, along a Mediterranean temperature range (sites at the same latitude), were conducted: one explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…Nonetheless, our dataset encompassing longer, and larger scale variability showed that populations living close to the warm edge of their distribution are indeed impacted by the increase in annual SST and SST aug . This hypothesis is further supported by a previous study showing a negative relationship between P. oceanica production and the number and duration of MHWs per year, and a decrease in phenological traits with increasing summer temperature across a longitudinal gradient (from Italy to Greece and Cyprus; Stipcich et al ., 2022a), suggesting that eastern populations can be also affected by the fast warming at this part of the basin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, our dataset encompassing longer, and larger scale variability showed that populations living close to the warm edge of their distribution are indeed impacted by the increase in annual SST and SST aug . This hypothesis is further supported by a previous study showing a negative relationship between P. oceanica production and the number and duration of MHWs per year, and a decrease in phenological traits with increasing summer temperature across a longitudinal gradient (from Italy to Greece and Cyprus; Stipcich et al ., 2022a), suggesting that eastern populations can be also affected by the fast warming at this part of the basin.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper understanding of the impact of warming on P. oceanica meadows extending along the Greek Seas is crucial, given that their extent represents 71% of the total extent estimated for the P. oceanica meadows of the Eastern Mediterranean Sea (Pergent‐Martini et al ., 2021). However, the lack of historical baselines of seagrass dynamics in Greece (Gerakaris et al ., 2021) and the scarce and rather localized information on the potential response of these meadows to warming (Bennett et al ., 2022b; Stipcich et al ., 2022a,b) limits our comprehension on the impact of warming in this region and, thus, our capacity to design specialized mitigation measures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…light (Dattolo et al, 2017), water quality (Maxwell et al, 2014), nutrients (Pazzaglia et al, 2020), salinity (Tomasello et al, 2009), warming (Marín‐Guirao et al, 2018), among others] and over a wide range of spatial scales [e.g. between sites of the same region (Maxwell et al, 2014), between regions (Tuya et al, 2019), along with depth gradients (Dattolo et al, 2017), latitudinal gradients (Jahnke et al, 2019; Ruocco et al, 2022) and between seas (Nguyen et al, 2020; Pansini et al, 2021; Stipcich et al, 2022)]. It is important to note that conclusions on local adaptation on seagrasses have been derived not only from population genetic data, but also from the comparison of phenotypic responses to environmental stressors among populations.…”
Section: Introductionmentioning
confidence: 99%